Using Bluetooth beacon technology to reduce distracted pedestrian behaviour: a cross-over trial study protocol. Issue 3 (30th December 2019) - Schwebel, David C; Hasan, Ragib; Griffin, Russell
Abstract : Objective: Over 6400 American pedestrians die annually, a figure that is currently increasing. One hypothesised reason for the increasing trend is the role of mobile technology in distracting both pedestrians and drivers. Scientists and policy-makers have attended somewhat to distracted driving, but attention to distracted pedestrian behaviour has lagged. We will evaluate Bluetooth beacon technology as a means to alert and warn pedestrians when they approach intersections, reminding them to attend to the traffic environment and cross streets safely. Methods: Bluetooth beacons are small devices that broadcast information unidirectionally within a closed proximal network. We will place beacons at an intersection frequently trafficked by urban college students. From there, the beacons will transmit to an app installed on users' smartphones, signalling users to attend to their environment and cross the street safely. A cross-over trial will evaluate the app with 411 adults who frequently cross the target intersection on an urban university campus. We will monitor those participants' behaviour over three distinct time periods: (1) 3 weeks without the app being activated, (2) 3 weeks with the app activated and (3) 4 weeks without the app activated to assess retention of behaviour. Throughout the 10-week period, we will gather information to evaluate whether the intervention changes distracted pedestrian behaviour using a logistic regression to estimate the likelihood of key behavioural outcome measures and adjusting for any residual confounding. We also will test for changes in perceived risk. The trial will follow CONSORT (Consolidated Standards of Reporting Trials) statement guidelines, as modified for cross-over design studies. Conclusion: If this program proves successful, it offers exciting implications for future testing and ultimately for broad distribution to reduce distracted pedestrian behavior. We discuss issues of feasibility, acceptability and scalability.